21 Understanding foreign accent syndrome. (28th May 2019) - McWhirter, Laura; Miller, Nick; Campbell, Catriona; Hoeritzauer, Ingrid; Lawton, Andrew; Carson, Alan; Stone, Jon
Abstract : Objectives/Aims: Foreign accent syndrome (FAS) is a disorder of speech in which listeners perceive the affected individual as speaking with a foreign or different regional accent that is not their habitual accent. FAS is widely understood as an unusual consequence of stroke or other lesions within speech-motor networks. However, case reports of FAS occurring in the absence of structural damage and difficulty identifying neural correlates has led to increasing recognition that that FAS sometimes represents a functional neurological disorder. We aimed to characterise symptoms, comorbidities, and features of recorded speech in individuals with self-reported FAS. Methods: Participants self-reporting FAS recruited from informal unmoderated online support forums and recruited via professional networks completed an online survey. Recorded samples of spontaneous speech and reading of a standardised text were analysed in a subgroup of 13 cases. Results: Forty-nine respondents (24 UK, 23 North America, 2 Australia) reported FAS of mean duration three years (range two months – 18 years). Common triggers were: migraine/severe headache (15), stroke (12), surgery or injury to mouth or face (six), and seizure (five, including three non-epileptic). High levels of comorbidity included migraine (33), irritable bowel syndrome (17), functional neurological disorder (12), and chronic pain (12). Five reported structural lesions on imaging. Author consensus on aetiology divided into, 'probably functional' (n=35, 71%), 'possibly structural' (n=4, 8%), and 'probably structural'(n=10, 20%), but positive features of functional FAS were present in all groups. Blinded analysis of speech recordings supplied by 13 respondents correctly categorised 11 (85%) based on probable aetiology (functional vs structural) in agreement with case history assignment. Analysis of speech recordings identified a range of features demonstrating internal inconsistency with potential utility in the diagnosis of functional FAS. Conclusions: This study, of the largest FAS case series to date, details the experience and characteristics of individuals with self-reported FAS, and describes an approach to auditory-perceptual analysis of speech with potential diagnostic utility. Although conclusions are limited by the recruitment methods, high levels of functional comorbidity, symptom variability and additional linguistic and behavioural features suggest that chronic FAS may in many cases represent a functional neurological disorder, even when a structural lesion is present.